The grounding of general and differentiated approaches to the complex treatment-rehabilitation help to co-dependent family of men with alcoholic addiction - Ярий, Володимир Володимирович (ScienceRise: Medical Science, 2016)
Aim – The grounding of general and differentiated approaches to the complex treatment-rehabilitation help to co-dependent family of men with alcoholic addiction (AA). Contingent. 160 men with AA and their wives and also 50 married couples, women, whose husbands had not alcoholic problems. Methods. Clinical-psychopathological and psychodiagnostic using the battery of AUDIT-like tests, elaborated by the composite authors under the guidance of I.V. Linsky and also the scales of anxiety and depression of M. Hamilton HDRS and HARS, the scale of assessment of psychosocial stress level of L. Reader and the methodology of determination of stress-resistance and social adaptation of Holms and Rahe. Psychosocial features of functioning of women were studied by psychodiagnostic method using the methodology of “Determination of subjective control level” of J. Rotter (in adaptation of E. F. Bagin) and questionnaire “The methods of overcoming behavior” of S. Folkman, R. Lazarus (in adaptation of L. I. Vasserman, E. A. Trifonova); the features of family functioning, inherent to examined persons, were established using methodology of “Analysis of family anxiety” of E. Eidemiller, B. Yustitskis and the scale of structural interview for identification of family type of V. A. Abramov and co-authors. Results. The aim of complex treatment-rehabilitation help for co-dependent family is an activation of the resource adaptive possibilities of the family and formation of the ability in men in women to solve the private and family problems (of alcoholic and non-alcoholic genesis) independently. The main directions, additional foundations, principles and conditions of realization of the complex treatment-rehabilitation help to co-dependent family were determined. The algorithm of its use was created. Psychotherapeutic component of treatment-rehabilitation process was characterized. It was accented, that psychotherapeutic work with co-dependent wives of patients with AA must have more differentiated character and be individualized, depending, first of all, on the clinical variant of women’s existent maladjustment and the type of family maladjustment co-dependence (FMC). The given parameters become the main criteria of differentiation of psychotherapeutic influences at determination of the content filling of psychotherapeutic interventions and also “sensitivity” to the different psychotherapeutic techniques. Conclusions. The positive result of introduction of this system becomes possible not only at the expense of using the treatment-rehabilitation influences but also in connection with positive changes of social and family relations of women (acceptance of social environment (context), where she lives and functions)